2009
DOI: 10.1097/prs.0b013e31818236d7
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Body Granulomas after All Injectable Dermal Fillers: Part 1. Possible Causes

Abstract: Summary Genuine granuloma formation following implantation of injectable dermal fillers is a rare complication, with incidences ranging from one in 100 patients (1 percent) to one in 5000 (0.02 percent). Foreign body granulomas occur several months to years after injection at all implantation sites at the same time. Without treatment, they may grow to the size of beans, remain virtually unchanged for some years, and then resolve spontaneously. Three clinical and histologic types of foreign body granulomas can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
243
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(260 citation statements)
references
References 111 publications
4
243
0
3
Order By: Relevance
“…These results were similar to those reported in the literature for other sites of PMMA implantation [7,20,31,32].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results were similar to those reported in the literature for other sites of PMMA implantation [7,20,31,32].…”
Section: Discussionsupporting
confidence: 82%
“…The microsphere sizes followed the recommendations of previous studies that showed that the use of 30-50 µm diameter particles prevented phagocytosis and migration [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Une injection traumatique qui dissèquerait le plan sous-épidermique (en éventail, injection rapide, volume important) ou trop superficielle, augmenterait le risque d'effets aigus ou inesthétiques : ecchymoses, hématomes, douleurs et nodules [26]. En cas d'injection avec une aiguille de trop gros diamètre, le produit pourrait former un nodule dans le tunnel laissé par l'aiguille [27]. L'injection rapide d'un volume important d'AH (plus de 2 ml/site) pourrait se comporter comme un implant conduisant à la formation d'une capsule qui se contracterait de la même manière que les contractures capsulaires mammaires [28].…”
Section: Discussionunclassified
“…Uncommon non-allergic adverse reactions include bacterial infection, aseptic or cold abscess, herpes reactivation [29], generalized scleromyxedema [30], scar sarcoidosis [31], interferon-induced systemic sarcoidosis in patients with chronic hepatitis C [32], and necrosis and livedoid pattern due to accidental arterial embolization [33]. Migration of the filler into a tunnel or track created by a large needle or cannula may manifest as a single and well-defined nodule 1-2 months after injection and may persist until resorption [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…However, a few cases of hypersensitivity and foreign body reaction have been documented, usually developing within 6-24 months [5][6][7][8][9][10][11][12][13][14][15]35].…”
Section: Discussionmentioning
confidence: 99%